Report of the Committee on the Elimination of Racial Discrimination, Seventy-sixth Session - United Nations Department for General Assembly; Conference Management (United Nations, 2022)
This is the annual report submitted to the General Assembly by the Committee on the Elimination of Racial Discrimination on its one hundred and first (4–7 August 2020), one hundred and second (16–24 November 2020) and one hundred and third (19–30 April 2021) sessions.